2020
DOI: 10.5539/jgg.v12n1p65
|View full text |Cite
|
Sign up to set email alerts
|

Wrench Tectonism and Intracontinental Basin Sedimentation: A Case Study of the Moku Sub-Basin, Upper Benue Trough, Nigeria

Abstract: The Upper Benue trough of Nigeria consists of basins and horsts characterized by numerous structural features. Detailed study of one of the basins revealed sets of “centimetric”, riedel type “en-echelon” NE-SW trending strike slip faults contained in a number of brittle and ductile shear zones characterizing the basement/sediment boundary. Structural analysis suggests that the Moku sub-basin has been pulled apart along a releasing bend in between NE – SW strike slip faults and that three principal axes of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Mbéri Kongo (2018) showed that the Cretaceous sandstones deposits of the Bateké Plateau on the margin of the Congo Basin have been deformed by large strike‐slip faults with associated conjugate normal faults. Northwest of the Oubanguides Belt, in West Africa, the Cretaceous intracratonic Benue Rift developed within the Trans‐Sahara Mobile Belt as a corridor of transtensive faults with associated magmatism (Ajakaiye et al., 1986; Benkhelil, 1989; Oha et al., 2020). The closure and abortion of the rift occurred in the Santonian, associated with a transpressional deformation of its Cretaceous syn‐rift deposits (Benkhelil, 1989; Ofoegbu, 1985).…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%
“…Mbéri Kongo (2018) showed that the Cretaceous sandstones deposits of the Bateké Plateau on the margin of the Congo Basin have been deformed by large strike‐slip faults with associated conjugate normal faults. Northwest of the Oubanguides Belt, in West Africa, the Cretaceous intracratonic Benue Rift developed within the Trans‐Sahara Mobile Belt as a corridor of transtensive faults with associated magmatism (Ajakaiye et al., 1986; Benkhelil, 1989; Oha et al., 2020). The closure and abortion of the rift occurred in the Santonian, associated with a transpressional deformation of its Cretaceous syn‐rift deposits (Benkhelil, 1989; Ofoegbu, 1985).…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%